Horizons of Phenomenology Essays on the State of the Field and Its Applications - Yoshimi, Jeff; Walsh, Philip; Londen, Patrick (Contributions to Phenomenology, 2023)
This is an open access book which explores phenomenology as both an exceptionally diverse movement in philosophy as well as an active research method that crosses disciplinary boundaries. The volume brings together lively overviews of major areas and schools of phenomenology, as well as the most recent applications across a range of fields. The first part reviews the state-of-the-art in various areas of contemporary phenomenology, including several distinct schools of Husserl and Heidegger scholarship, as well as approaches derived from Merleau-Ponty, de Beauvoir, Fanon, and others. An innovative quantitative analysis of citation networks provides rich visualizations of the field as a whole. The second part showcases phenomenology as a living discipline that can advance research in other areas. While some areas of interaction between phenomenology and other disciplines are by now well established (e.g. cognitive science), this volume sheds light on newer areas of application. The goal is to move beyond discussions of philosophical method and highlight scholars who are actually doing phenomenology in a variety of areas, including: Embodiment and questions of gender, race, and identity, The arts (visual art, literature, architecture), and Archaeology and anthropology. This volume offers a concise introduction to cutting edge phenomenological research and is suitable for both students and specialists.